2023
DOI: 10.37074/jalt.2023.6.1.29
|View full text |Cite
|
Sign up to set email alerts
|

The role of ChatGPT in higher education: Benefits, challenges, and future research directions

Abstract: This paper examines the potential benefits and challenges of using the generative AI model, ChatGPT, in higher education, in the backdrop of the constructivist theory of learning. This perspective-type study presents five benefits of ChatGPT: the potential to facilitate adaptive learning, provide personalised feedback, support research and data analysis, offer automated administrative services, and aid in developing innovative assessments. Additionally, the paper identifies five challenges: academic integrity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(67 citation statements)
references
References 95 publications
3
63
0
1
Order By: Relevance
“…AI chatbots offer the promise of personalised, adaptive learning and immediate feedback (Zhao et al, 2021). Yet, they also pose challenges to the authenticity of learning outcomes, as they can be misused to bypass conventional online assessments (Daniel, 2020), creating both unethical and inequalities issues (Rasul et al, 2023). This duality raises the question of how to benefit from the potential of AI without compromising assessment integrity.…”
Section: Ai Chatbots: a Double-edged Swordmentioning
confidence: 99%
See 3 more Smart Citations
“…AI chatbots offer the promise of personalised, adaptive learning and immediate feedback (Zhao et al, 2021). Yet, they also pose challenges to the authenticity of learning outcomes, as they can be misused to bypass conventional online assessments (Daniel, 2020), creating both unethical and inequalities issues (Rasul et al, 2023). This duality raises the question of how to benefit from the potential of AI without compromising assessment integrity.…”
Section: Ai Chatbots: a Double-edged Swordmentioning
confidence: 99%
“…They can also assist in formative assessments, providing immediate feedback on students' progress and guiding them towards improvement (Siemens et al, 2015). According to Rasul et al, (2023), the utilisation of chatbot technology has demonstrated beneficial impacts on various aspects of the learning process, including the enhancement of explicit reasoning capabilities, improvements in learning outcomes and knowledge retention, as well as a heightened interest and engagement in the learning process.…”
Section: The Promising Edge: Advantages Of Ai Chatbotsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since then, we have fostered a rich dialogue by publishing more than 20 substantial pieces on this pressing subject. Our journal has become a focal point for critical discussions encompassing the potential advantages, challenges, and actionable recommendations concerning the implementation of generative AI technologies such as ChatGPT, as documented in a series of articles (Firat, 2023;Gamage et al, 2023;Ifelebuegu et al, 2023;Limna et al, 2023;Rasul et al, 2023;Rudolph et al, 2023aRudolph et al, , 2023b. Furthermore, our contributors have rigorously explored the ethical dimensions surrounding academic integrity and student engagements with AI tools during assessments, providing nuanced analyses of this complex issue (Chaka, 2023;Hassoulas et al, 2023;Ifelebuegu, 2023;Mohammadkarimi et al, 2023;Sullivan et al, 2023).…”
Section: Introductionmentioning
confidence: 99%